Novel Essential Gene Involved in 16S rRNA Processing in Escherichia coli. Issue 4 (27th February 2015) - Kurata, Tatsuaki; Nakanishi, Shinobu; Hashimoto, Masayuki; Taoka, Masato; Yamazaki, Yukiko; Isobe, Toshiaki; Kato, Jun-ichi
Abstract: Biogenesis of ribosomes is a complex process mediated by many factors. While its transcription proceeds, ribosomal RNA (rRNA) folds itself into a characteristic three-dimensional structure through interaction with ribosomal proteins, during which its ends are processed. Here, we show that the essential protein YqgF, a RuvC family protein with an RNase-H-like motif, is involved in the processing of pre-16S rRNA during ribosome maturation. Indeed, pre-16S rRNA accumulated in cells of a temperature-sensitive yqgF mutant ( yqgF ts ) cultured at a non-permissive temperature. In addition, purified YqgF was shown to process the 5′ end of pre-16S rRNA within 70S ribosomes in vitro . Mass spectrometry analysis of the total proteins in the yqgF ts mutant cells showed that the expression of genes containing multiple Shine–Dalgarno-like sequences was observed to be lower than in wild type. These results are interpreted to indicate that YqgF is involved in a novel enzymic activity necessary for the processing of pre-16S rRNA, thereby affecting elongation of translation. Graphical abstract: Highlights: Escherichia coli essential protein YqgF, a RuvC family protein with an RNase-H-like motif. Accumulation of pre-16S rRNA in cells of a temperature-sensitive yqgF mutant. In vitro processing of 5′ end of pre-16S rRNA within 70S ribosomes by purified YqgF. Lowered expression of genes containing multiple Shine–Dalgarno-like sequences. YqgF involved in ribosome maturation and elongation of translation.